Zirconia‐containing glass‐ceramics: From nucleating agent to primary crystalline phase - Adam Shearer; Maziar Montazerian; Binghui Deng; Jessica J. Sly; John C. Mauro (International Journal of Ceramic Engineering & Science, 2024)
Abstract This article reviews promising studies on the design, manufacturing, microstructure, properties, and applications of glass‐ceramics containing ZrO2 and relevant glass‐ceramic matrix composites. After the addition of ZrO2 to a glass‐ceramic composition, it can persist in the residual glassy phase, facilitate nucleation, and/or precipitate as ZrO2 or another zirconate crystalline phase. Also, ZrO2‐reinforced or ZrO2‐toughened glass‐ceramics can be designed as composites. In this article, the term “ZrO2‐containing glass‐ceramics” encompasses all these scenarios in which ZrO2 is present. Such glass‐ceramics offer a wide range of applications in modern industries, including but not limited to architecture, optics, dentistry, medicine, and energy. Since S. Donald Stookey's discovery of glass‐ceramics in the early 1950s, the most important scientific efforts reported in the literature are reviewed. ZrO2 is commonly added to glass‐ceramics to promote nucleation. As a result, the role of ZrO2 in structural modification of residual glass and stimulating the nucleation in glass‐ceramic is first discussed. ZrO2 can also be designed into the main crystalline phase of glass‐ceramics, contributing achieving super high fracture toughness above 4 MPa·m0.5. Experimental and computational studies are reviewed in detail to elucidate how the transformation toughening and other mechanisms help to achieve such high values of fracture toughness. Sintered and glass‐ceramic matrix composites also show promise, where ZrO2 contributes to improved stability and mechanical properties. Finally, we hope this article will provoke interest in glass‐ceramic materials in both the scientific and industrial communities so that their tremendous technological potential in developing, for example, tough, thermally stable, transparent, and biologically compatible materials can be realized more widely.